Design and Evaluation of a Modulated TENS Stimulation in Medical Pain Therapy - Bouafif, L.; Ellouze, N. (Current Signal Transduction Therapy, 2019)
Background: Transcutaneous Electrical Nerve Stimulation (TENS) is a non-invasive pain therapy that uses the sensory effects of an electrical current applied to the skin. Some clinical studies demonstrated that this treatment helps to reduce acute and chronic pains, while others gave sometimes contradictory or uncertain conclusions about the performances of this strategy according to pathology classification. The purpose of this study is the development and evaluation of a new modulated version of transcutaneous electrical nerve stimulation called PWM-TENS. The principle is based on an automatic variation of the stimulation parameters (frequency, amplitude, duration, shape, cyclic ratio) according to the pain evolution. Methods: The study was a controlled clinical trial involving 15 participants, divided into 2 groups. The first experimental group performed modulated PWM-TENS electro-stimulation sessions applied to the painful areas 3 to 4 times a day, for one month. The second control group did parallel treatments by Placebo. The evaluation of the pain intensity is done with the Visual Analog Scale (EVA), the DN4 and SF36 questionnaires. Results: The tests and measurements with our embedded PWM-TENS technique demonstrated that we succeeded to increase the analgesic effect after stopping the stimulation and reduced the pain sensation by about 60%. An improvement in pain intensity scores and questionnaires (EVA, DN4), as well as the quality of life score (SF36), was observed. Also, a reduction of the treatment period from 3 to 1 month was also obtained. Conclusion: The first results clinically observed in the PWM-TENS technique are encouraging. The findings of this study confirm that this noninvasive strategy is suitable and useful for acute pains coming from the nociceptive, neuropathic and musculoskeletal origin. However, its efficiency is moderated and less adapted for low back pain. The experiments make it possible to estimate whether this modulated TENS method could improve existing anti-pain therapies, taking into account objective and subjective evaluation criteria. But this study must be followed by large population samples to answer all the problems of acute and chronic pains.
Keywords: pain transmission